RETHINKING TEORI KOMUNIKASI DALAM KONTEKS MEDIA BARU (Telaah Pemikiran Holmes tentang Komunikasi, Teknologi dan Masyarakat) - Sih Natalia Sukmi (Universitas Kristen Satya Wacana, 2015)
The new media give consequence to the study of communication sciences. Empirical facts showed that communication research often get stuck on the wrong footing basis in analyzing social conditions, but there is no doubt that the theory of communication should be in harmony with the development of technologies that facilitate society and interaction process. This study seeks to provide a description of how the development of the theory of communication and dialogue with communication problems emerging. David Holmes's view on the development of communication studies will overshadow this article. Literature method used to describe the theories that have been and can be applied to the study of communication, new media and social implications there in.Keywords: Theory of communication, new media, David Holmes